PENGGUNAAN METODE DISKUSI UNTUK MENGAKTIFKAN SISWA KELAS 2 SEKOLAH DASAR PADA MATA PELAJARAN MATEMATIKA - Veronika Yuliana Beku; Nasarius Sensius Bate; Yosefa Kafasin Owa Owa; Maria Yunita Lajo; Algiana Yuliamat Rasapril Jaun; Yosefina Uge Lawe (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2023)
Abstract The use of inappropriate learning methods can result in mathematics learning not being able to attract students' attention. This can cause students to be less active, low student learning outcomes and learning objectives cannot be achieved effectively. Therefore, as a teacher, you must be able to choose the right method that can increase student activity so that students can understand learning well. The method used is the discussion method. The purpose of this writing is to find out the application of the discussion method in learning elementary school mathematics. This article aims to analyze the use of the discussion method to increase the activity of 2nd grade elementary school students. The use of the discussion method can provide an overview of how the methods and interactions that occur can meet the indicators of active learning in the form of motivation and enthusiasm for participating in learning activities. The use of the discussion method is very well used for student activity problems and supports the achievement of learning objectives